(untitled) (Community Based Medical Journal, 2025)
Patients with chronic kidney disease (CKD) have a high prevalence of vitamin D deficiency; such a deficiency can exacerbate the CKD and related complications. The population in Bangladesh gets exposure to sunlight radiation; however, levels of vitamin D levels could be affected due to factors like skin color, dressing etiquette, etc. This cross-sectional study was done in Community Based Medical College, Bangladesh (CBMC,B) Hospital, from January 2021 to January 2022, to determine the prevalence vitamin D deficiency among of CKD patients and to examine association between vitamin D and CKD classification. A total of 120 patients who had been diagnosed with CKD (stages 3-5) were included in this study. Data on age, gender, past medical history, and blood samples for serum creatinine and 25-hydroxyvitamin D levels were obtained. The eGFR was estimated from the CKD-EPI formula. Serum (>30 ng/mL) levels were classified into a normal range, which was greater than 30 ng/mL, insufficient, between 10 and 30 ng/mL, and deficient if lower than 10 ng/mL. The mean age of the study participants was 53.25±7.6 years, with 66.7% male. Vitamin D deficiency was found in 25% of patients, while 35.8% had insufficiency. A significant inverse relationship was observed between CKD stages and mean vitamin D levels (p<0.00001). Mean vitamin D levels decreased from 33.53±6.24 ng/mL in stage 3a to 12.36 ± 3.43 ng/mL in stage 5. Our study gives an indication that vitamin D deficiency and insufficiency are considerable among the CKD patients in Bangladesh, and it correlates significantly with the severity of kidney disease. Hence, we recommend vitamin D monitoring and possibly supplementation in the context of CKD, especially in the late stages. CBMJ 2025 January: Vol. 14 No. 01 P: 4-10